Subsonic Flutter of Cantilever Rectangular PC Plate Structure - Kemal Yaman (International Journal of Aerospace Engineering)
Flutter characteristics of cantilever rectangular flexible plate structure under incompressible flow regime are investigated by comparing the results of commercial flutter analysis program ZAERO© with wind tunnel tests conducted in Ankara Wind Tunnel (ART). A rectangular polycarbonate (PC) plate, 5 × 125 × 1000 mm in dimension, is used for both numerical and experimental investigations. Analysis and test results are very compatible with each other. A comparison between two different solution methods (g-method and k-method) of ZAERO© is also done. It is seen that the k-method gives a closer result than the other one. However, g-method results are on a conservative side and it is better to use conservative results, namely, g-method results. Even if the modal analysis results are used for the flutter analysis for this simple structure, a modal test should be conducted in order to validate the modal analysis results to have accurate flutter analysis results for more complicated structures.